60th Anniversary of Hungarian Plant Protection Service - Pálmai, Ottó (Acta Agraria Debreceniensis, 2014)
The author briefly overview the history of the 60-year-old Hungarian Plant Protection Service, which has improved to a model by its ’golden age’ period with a well organized system and excellence of specialists on the chemistry period of Hungarian agriculture. The profound changes both in policy and economy resulted a serious structural changes which continue even nowadays. Meanwhile country borders have been opened than EU membership of Hungary have generated new challenges by appearance and spread of new pests.